Answer:
a. Increasing
b. Increasing
c. Decreasing
Step-by-step explanation:
Part A (g(x) = 4x – 2)
![\begin{gathered} g(2)=4(2)-2=8-2=6 \\ g(1)=4(1)-2=4-2=2 \\ (g(2)-g(1))/(2-1)=(6-2)/(1) \\ =(4)/(1) \\ =4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/6e1pq3o3gwvvby6qdrtbfp0ayzmppu7kpt.png)
g(x) is increasing since its rate of change is positive.
Part B (f(x) = 3x)
![\begin{gathered} f(2)=3(2)=6 \\ f(1)=3(1)=3 \\ (f(2)-f(1))/(2-1)=(6-3)/(1) \\ =(3)/(1) \\ =3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/wzxfakyn7etmfsfxsza8ecpr0acuax3cei.png)
f(x) is increasing since its rate of change is positive.
Part C (h(x) = 2-x)
![\begin{gathered} h(2)=2-2=0 \\ h(1)=2-1=1 \\ (h(2)-h(1))/(2-1)=(0-1)/(1) \\ =(-1)/(1) \\ =-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/f0ziz9ovj1ry3eeemdy9o7arqriv2ssvs3.png)
h(x) is decreasing since its rate of change is negative.